2004
DOI: 10.1259/dmfr/31287277
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of premolar tooth lengths based on their panoramic radiographic lengths

Abstract: Prediction of all first premolar lengths using their panoramic images is both feasible and reliable.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
7
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 7 publications
1
7
1
Order By: Relevance
“…They have found that the magnification is similar on the right and left sides (Yitschacky et al, 2004), which is similar to the results of the present study. However, in these studies the magnification was greater in the maxilla than in the mandible, contrary to what was found in the present work.…”
Section: Discussionsupporting
confidence: 92%
“…They have found that the magnification is similar on the right and left sides (Yitschacky et al, 2004), which is similar to the results of the present study. However, in these studies the magnification was greater in the maxilla than in the mandible, contrary to what was found in the present work.…”
Section: Discussionsupporting
confidence: 92%
“…In reality, this ideal is unattainable, and thus dimensional accuracy of panoramic radiography is often impossible. With this in mind, magnification has been reported to range between 14% and 26% 6,7 ; however, in this study, magnification was between 27.5% and 29.3%. In this in-vitro experiment, the reported ideal anteroposterior angulation was 90 to the horizontal plane (floor); this is not equivalent to the ideal cephalometric angulations for the maxillary incisors (110 to the palatal plane) or the mandibular incisors (95 to the mandibular plane).…”
Section: Discussioncontrasting
confidence: 59%
“…1990a). From one study which calculated the difference in radiographic estimated root length compared to actual root length of completed first premolars a regression model was formulated to accurately predict root length (Yitschaky et al. 2004).…”
Section: Discussionmentioning
confidence: 99%